The nurse training in research in the undergraduate education: teaching perceptions - Aluana Moraes; Maria Helena Dantas de Menezes Guariente; Mara Lúcia Garanhani; Brígida Gimenez de Carvalho
ABSTRACT Objective: To analyze how the approach of the theme "scientific investigation" can contribute to the development of the scientific competence of the Nursing student. Method: A descriptive-exploratory, case-study, qualitative study was carried out with professors from a public university in the South of Brazil. Data were collected through a semi-structured individual interview and a group interview, called the conversation circle. Results: Data analysis consisted of three categories: "Research as a structuring theme and scientific principle in undergraduate student training in Nursing"; "Research as a structuring theme and scientific principle in undergraduate student training in Nursing"; "Sap research and educational principle in the integrated curriculum". Conclusion: Research training can occur at all undergraduate academic moments, providing the student with the knowledge of scientific research as a formative content and as an investigative attitude, in order to enable the development of scientific competence in professional practice.